Interaction With Nontypeable Haemophilus influenzae Alters Progression of Streptococcus pneumoniae From Colonization to Disease in a Site-Specific Manner. (23rd June 2019) - Lewnard, Joseph A; Givon-Lavi, Noga; Dagan, Ron
Abstract: Background: Pneumococci and nontypeable Haemophilus influenzae (NTHi) often cocolonize children. The impact of species interactions on disease risk across the upper respiratory mucosa is not known. Methods: We analyzed data from 4104 acute conjunctivitis (AC) cases, 11 767 otitis media (OM) cases, and 1587 nasopharyngeal specimens collected from Israeli children before pneumococcal conjugate vaccine introduction. We compared pneumococcal serotype distributions with NTHi present and absent, and compared single-species and mixed-species rates of serotype-specific progression from colonization to AC and OM. Results: Pneumococcal serotypes causing single-species OM (NTHi absent) were less diverse than colonizing serotypes and also less diverse than those causing mixed-species OM; colonizing and OM-causing pneumococcal serotype distributions were more similar to each other with NTHi present than with NTHi absent. In contrast, serotype diversity did not differ appreciably between colonizing and AC-causing pneumococci, regardless of NTHi co-occurrence. The similarity of colonizing and AC-causing pneumococcal serotype distributions was consistent in the presence and absence of NTHi. Differences in rates that pneumococcal serotypes progressed from colonization to disease were reduced in both AC and OM when NTHi was present. Conclusions: Interactions with NTHi may alter progression of pneumococcal serotypes to diseases of the upper respiratory mucosa in a site-specific manner. Abstract : An epidemiologic analysis suggests the capacity of pneumococcal serotypes to cause otitis media is more tightly restricted than their capacity to cause acute conjunctivitis. Nontypeable Haemophilus influenzae may facilitate progression of a wider selection of pneumococcal serotypes to otitis media.